Method for testing the fatigue resistance of copper foil
By bending and flattening the copper foil, it simulates its stress in the battery cell, and conducts tensile testing, the problem that existing testing methods cannot effectively characterize the fatigue resistance of copper foil, and realizes accurate evaluation of the performance of copper foil and identification of batch differences.
Patent Information
- Application Number
- CN202211152967.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-09-21
AI Technical Summary
The existing testing methods cannot effectively characterize the fatigue resistance of copper foils, especially when the copper foil is under stress during the charging and discharging of the battery cell, the differences between different batches of copper foils cannot be identified, resulting in an increase in production risk.
By bending and flattening the copper foil, creases are formed and pressure is applied to simulate its tensile and contracting state in the battery cell, and then tensile tests are performed on the cut test sample to evaluate its tensile strength and elongation to characterize fatigue resistance.
This method can effectively simulate the stress condition of copper foil in the battery cell, accurately characterize its fatigue resistance, and better identify the differences between different batches of copper foils, reducing production risks.
Smart Images

Figure CN115493903B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for testing the fatigue resistance of copper foil. Background Art
[0002] Currently, with the expansion of market demand and applications, the energy density requirements for lithium-ion batteries are becoming increasingly higher, while also taking into account multiple important performance factors such as high safety and long cycle life. Silicon-based materials, as the preferred material for negative electrodes, can significantly increase the energy density of lithium-ion batteries. However, due to the large expansion of silicon-based negative electrodes themselves, this leads to the problem of high expansion of the battery cells. During the charge and discharge process of the battery cell, the copper foil serving as the negative electrode current collector is affected by the volume changes of the negative electrode material. The copper foil is repeatedly stretched and contracted in its non-thickness direction, resulting in splits, cracks, and even fragmentation.
[0003] Existing test methods (such as GB / T 228.1-2010 and the test methods for tensile strength and elongation of copper foil in IPC-TM-650) can no longer quickly screen out ultra-thin, high-strength, and high-toughness lithium battery copper foil suitable for production and meeting the extremely harsh conditions during use from a wide variety of copper foil products. In addition, the existing test methods cannot reflect the state of the copper foil when it shrinks when testing the tensile strength and elongation of the copper foil. As a result, the fatigue resistance of the copper foil cannot be fully characterized, resulting in the inability to well identify the differences between different batches of copper foil, which brings great risks to production.
[0004] The introduction of new testing methods is a trend that requires it and has important practical significance. Summary of the Invention
[0005] Aiming at the problem that the existing battery core copper foil testing method cannot effectively characterize the fatigue resistance of the copper foil, the present invention provides a method for testing the fatigue resistance of the copper foil.
[0006] In order to achieve the above object, the present invention provides a method for testing the fatigue resistance of copper foil, which comprises:
[0007] (1) bending the copper foil and applying a first pressure to obtain a bent copper foil, wherein the bent copper foil has a crease formed by the bending;
[0008] (2) unfolding the bent copper foil and applying a second pressure to the fold to obtain a flat copper foil;
[0009] (3) cutting at least a portion of the flat copper foil as a test sample, wherein the test sample contains at least a portion of the crease;
[0010] (4) Performing a tensile test on the test sample, and evaluating the fatigue resistance of the copper foil based on the measured tensile strength and elongation.
[0011] The present invention fully takes into account that during the charging and discharging process of the battery cell, the negative electrode copper foil is subjected to force in the non-thickness direction and is in two states of stretching and contraction, and these two states are continuously and repeatedly switched. Based on this, the inventors of the present invention adopt bending and flattening operations on the copper foil, which can well simulate the stretching and contraction of the copper foil in the battery cell as the volume of the negative electrode material changes due to lithium removal and insertion. The copper foil that has undergone the above-mentioned bending and flattening operations is then subjected to a tensile test, thereby effectively characterizing the fatigue resistance of the copper foil and better identifying the differences between different batches of copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following detailed description, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0013] Figure 1 Schematic diagram of the bending angle of the copper foil in the method for testing the fatigue resistance of the copper foil of the present invention.
[0014] Figure 2 This is a schematic diagram of the operation when the bending angle of the copper foil is less than 180° in the method for testing the fatigue resistance of the copper foil according to one embodiment of the present invention.
[0015] Description of Reference Numerals
[0016] a, β, γ rotation angle i, inner mold ii, outer mold
[0017] F. Copper foil DETAILED DESCRIPTION
[0018] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0019] The present invention provides a method for testing the fatigue resistance of copper foil, the method comprising:
[0020] (1) bending the copper foil and applying a first pressure to obtain a bent copper foil, wherein the bent copper foil has a crease formed by the bending;
[0021] (2) unfolding the bent copper foil and applying a second pressure to the fold to obtain a flat copper foil;
[0022] (3) cutting at least a portion of the flat copper foil as a test sample, wherein the test sample contains at least a portion of the crease;
[0023] (4) Performing a tensile test on the test sample, and evaluating the fatigue resistance of the copper foil based on the measured tensile strength and elongation.
[0024] According to the present invention, the copper foil can be any metal foil primarily composed of copper, and the present invention is not particularly limited thereto. Preferably, the copper foil is an electrolytic copper foil or a rolled copper foil suitable for use as a negative electrode current collector for lithium-ion batteries. The preparation methods and process parameters thereof are well known to those skilled in the art and will not be further described herein.
[0025] According to the present invention, preferably, the thickness of the copper foil is 3-30 μm, and the surface density is 25-270 g / cm 2 .
[0026] According to the present invention, in step (1), the copper foil is bent to form a fold on the copper foil, and a first pressure is applied to obtain a bent copper foil. In the present invention, the fold includes, at a microscopic level, an axis (a straight line along which the copper foil is bent) and a bent region of the copper foil near the axis.
[0027] According to the present invention, the direction of the fold formed by the bend is not particularly limited and can be in any direction. Preferably, the fold formed by the bend is parallel to the longitudinal direction (TD direction) or transverse direction (MD direction) of the copper foil. In the present invention, the longitudinal and transverse directions of the copper foil are both conventionally defined by those skilled in the art, that is, the direction in which the copper foil is unwound is the longitudinal direction, and the direction perpendicular to the direction in which the copper foil is unwound is the transverse direction.
[0028] According to the present invention, in step (1), the bending angle of the copper foil is 1-180°, preferably 90-180°, and more preferably 180°.
[0029] In the present invention, Figure 1 As shown, when the plane on one side of the crease is stationary and the plane on the other side rotates along the crease (i.e. Figure 1 For this type of bending, the bending angle refers to the angle that the plane rotates along the crease from the beginning to the end of the bending (i.e. Figure 1 angle α in the crease); when the planes on both sides of the crease rotate along the crease (i.e. Figure 1 For this bending method, the bending angle refers to the sum of the angles of the two planes rotated along the crease from the beginning to the end of the bending (i.e. Figure 1 β angle + γ angle in .
[0030] According to the present invention, in step (1), the first pressure is applied to the fold, so that the inner fold area of the bent copper foil is in a contracted state and the outer fold area is in a stretched state.
[0031] According to the present invention, in step (1), when the bending angle is 180°, the conditions for applying the first pressure include: the pressure direction is perpendicular to the surface of the copper foil; the pressure magnitude is 0.01-500kg, preferably 20-100kg; the time is 1-86400s, preferably 2-60s.
[0032] According to the present invention, in step (1), when the bending angle is 180°, for the operation process of obtaining the bent copper foil, preferably, the copper foil can be laid flat on a flat plate A, bent 180° under the action of an external force, and then another flat plate B is used to cover the crease, or a roller is used to press the crease (the outer crease of the copper foil is in contact with the flat plate B or the roller), and a first pressure perpendicular to the surface of the copper foil is applied to the crease by the flat plate B or the roller to obtain the bent copper foil.
[0033] In the present invention, in order to make the folds bear force more evenly, it is preferred to cover the folds with a flat plate and apply the first pressure via the flat plate.
[0034] According to the present invention, in step (1), when the bending angle is less than 180°, the conditions for applying the first pressure include: the direction of pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil; the pressure magnitude is 0.01-500kg, preferably 20-100kg; the time is 1-86400s, preferably 2-60s.
[0035] According to the present invention, in step (1), when the bending angle is less than 180°, the operation process for obtaining the bent copper foil is preferably as follows: Figure 2 As shown, an inner mold i and an outer mold ii with the same folding angle can be prepared, wherein the inner mold i and the outer mold ii both have smooth and flat inner surfaces; a copper foil is placed between the inner mold i and the outer mold ii, and then the inner mold i and the outer mold ii are overlapped and pressed, and a first pressure is applied to the crease through the mold i at the connection with the inner surface of the bent copper foil, and then the inner mold i and the outer mold ii are removed to obtain a bent copper foil.
[0036] According to a preferred embodiment of the present invention, in step (1), when the bending angle is less than 180°, the direction of applying the first pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil, and is along the bisector of the mold angle and perpendicular to the axis of the crease.
[0037] According to the present invention, in step (2), the bent copper foil is unfolded and a second pressure is applied to the fold, so that the inner fold area of the bent copper foil is in a stretched state and the outer fold area is in a contracted state.
[0038] According to the present invention, in step (2), the conditions for applying the second pressure include: the direction of pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil; the pressure magnitude is 0.01-500kg, preferably 20-100kg; the time is 1-86400s, preferably 2-60s.
[0039] According to the present invention, for the implementation process of step (2), preferably, the inner side of the bent copper foil can be faced upward and unfolded, and then placed on a flat plate A, and then another flat plate B is used to cover the crease, or a roller is used to press the crease (the inner crease of the copper foil is in contact with the flat plate B or the roller), and a second pressure is applied to the crease through the flat plate B or the roller to obtain a flat copper foil.
[0040] According to the present invention, step (1) and step (2) can be repeated. In the present invention, the repeated steps refer to sequentially performing step (1) and step (2) on the copper foil, and after step (2) is completed, the flat copper foil obtained is used as the processing object and sequentially subjected to step (1) and step (2), and the process is repeated.
[0041] According to the present invention, step (1) and step (2) are repeated 0-20 times, preferably 0-1 times.
[0042] According to the present invention, when steps (1) and (2) are repeated, the position of the fold formed each time is the same.
[0043] According to the present invention, when step (1) and step (2) are repeated, the bending performed at different times may adopt the same bending direction or different bending directions, and the present invention has no special limitation on this.
[0044] According to the present invention, when step (1) and step (2) are repeated, the application conditions of the first pressure and the second pressure may be the same or different in different operations, but are preferably the same.
[0045] According to the present invention, in step (3), the thickness of the test sample is the same as the thickness of the copper foil, and the shape of the test sample is rectangular.
[0046] According to the present invention, preferably, the test sample has a length of 20-200 mm and a width of 5-50 mm.
[0047] According to the present invention, in step (3), in the test sample, at least part of the fold is perpendicular to the length direction of the test sample and is equidistant from both ends of the test sample that are perpendicular to the length direction.
[0048] According to the present invention, in step (3), it should be emphasized that, for the test sample, except for the above-mentioned creases, no obvious mechanical damage is allowed, and no structural defects such as burrs and flash are allowed on the edges, otherwise the test results will be affected.
[0049] According to the present invention, in step (4), the tensile test is performed on a tensile testing machine. The specific operation can be referred to GB / T 228.1-2010. The two ends of the length direction of the test sample are respectively fixed to the two clamps of the tensile testing machine. The length direction of the test sample is adjusted so that the length direction of the test sample is parallel to the axis of the clamp, and the test sample is kept flat. Then, the testing machine is turned on to perform the test, and the test results of the tensile velocity and elongation are read. The average value is obtained after multiple tests. If, in a certain test, the position where the test sample breaks during stretching is not at the fold, the test data of this test will be discarded and not included in the results.
[0050] According to the present invention, in step (4), preferably, the conditions of the tensile test include: a tensile speed of 10-500 mm / min, preferably 50-100 mm / min.
[0051] The method for testing the fatigue resistance of copper foil provided by the present invention can be used to evaluate the fatigue resistance of copper foil based on the tensile test results of the test sample (i.e., the measured tensile strength and elongation). Specifically, a copper foil standard sample can be selected and determined first, and the copper foil standard sample can be tested using the method to obtain the tensile strength (denoted as Rm 标准样 ), elongation (denoted as δ 标准样 ) data; then using the method, and using the same test operation process and test parameters as the copper foil standard sample, the copper foil to be evaluated was tested to obtain the tensile strength of the copper foil to be evaluated (denoted as Rm 待测样 ), elongation (denoted as δ 待测样 ) data; compare the tensile strength and elongation data of the copper foil to be evaluated with the tensile strength and elongation data of the copper foil standard sample: when the tensile strength and elongation of the copper foil to be evaluated are not lower than those of the copper foil standard sample (i.e. Rm 待测样 ≥Rm 标准样 , and δ 待测样 ≥δ 标准样 ), it is considered that the fatigue resistance of the copper foil to be evaluated meets the requirements and can be used in the production of negative electrodes; when at least one of the tensile strength and elongation of the copper foil to be evaluated is lower than that of the copper foil standard sample, it is considered that the fatigue resistance of the copper foil to be evaluated cannot meet the requirements or has a greater risk of cracking during use.
[0052] In the present invention, the copper foil standard sample is defined as a qualified copper foil that can meet the use requirements and is routinely used by copper foil users (such as battery or negative electrode manufacturers). For example, a specific batch of samples can be selected from the incoming inspection samples provided by the supplier to the user before the bulk of the copper foil products purchased by the user enters the factory, or from the bulk of the copper foil products provided by the supplier. After the user prepares the sample into a battery negative electrode according to its own production process for actual inspection, if the test results are qualified and can meet the user's production and use requirements, the above-selected batch of samples can be used as the copper foil standard sample. The specifications of the copper foil standard sample (such as thickness, surface density and other conventional indicators specified in the industry) must be consistent with the subsequent copper foil to be evaluated, that is, using the test method of the present invention, a copper foil standard sample with the same specifications as the copper foil to be evaluated must be selected. Copper foil users can select and determine the copper foil standard sample based on their own requirements for the use of copper foil, referring to the definition of the above-mentioned copper foil standard sample. Typically, the copper foil conventionally used by each manufacturer is one or several specifications with fixed parameter index requirements. Accordingly, one or more copper foil standard samples can be selected and determined to meet the testing needs of possible copper foil products of different specifications.
[0053] The present invention will be described in detail below by way of examples.
[0054] The thickness of the copper foil standard sample (a qualified copper foil used in actual production) is 6μm and the surface density is 54g / cm 2 ;
[0055] The copper foil to be tested (copper foil from two production batches, the first batch and the second batch, with the same thickness and surface density) has a thickness of 6 μm and a surface density of 54 g / cm 2 .
[0056] Tensile testing machine: purchased from Haida International Instrument Co., Ltd., model HD-B609B-S.
[0057] Example 1
[0058] (1) Figure 1 As shown, a standard copper foil sample with a length and width of approximately 200*200 mm is placed on a smooth glass plate A. The copper foil is bent 180° (the fold is parallel to the longitudinal direction of the copper foil). The fold is covered with a smooth glass plate B (the outer fold of the copper foil is in contact with the glass plate B). A first pressure is applied to the fold through the glass plate B (the direction of the pressure is perpendicular to the copper foil surface, the pressure is 50 kg, and the pressure is applied for 2 seconds) to obtain a bent copper foil.
[0059] (2) The bent copper foil is unfolded with the inner side facing upwards and placed on glass plate A. The fold is then covered with glass plate B (the inner fold of the copper foil contacts the glass plate B). A second pressure is applied to the fold through glass plate B (the direction of the pressure is perpendicular to the surface of the copper foil, the pressure is 50 kg, and the pressure is applied for 2 seconds) to obtain a flat copper foil;
[0060] (3) Cut a rectangular copper foil with a length of 100 mm, a width of 15 mm, and a thickness of 6 μm from the above-mentioned flat copper foil as a test sample (in this test sample, the fold length is 15 mm, and the fold is perpendicular to the length direction of the test sample and is equidistant from the two ends of the test sample perpendicular to the length direction), and check to ensure that there is no obvious mechanical damage in the test sample except the fold line, and there are no burrs or flash on the edges;
[0061] (4) Adjust the original gauge length between the two clamps of the tensile testing machine to 50 mm, and fix the two ends of the length direction of the above-mentioned test sample on the two clamps respectively, wherein the length direction of the test sample is parallel to the axis of the clamp, and the test sample is kept flat; then turn on the testing machine for testing, and the test conditions include: the tensile speed is 50 mm / min, and the tensile speed and elongation data of the test sample are obtained.
[0062] The same steps (1) to (4) and parameters as above were used to test the copper foils to be tested (the first batch and the second batch) with a length and width of about 200*200 mm.
[0063] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., longitudinal tensile strength and longitudinal elongation) are shown in Table 1.
[0064] The same steps (1) to (4) and parameters as above were used, with the only difference being that the fold in step (1) was parallel to the transverse direction of the copper foil, and copper foils with a length and width of approximately 200*200 mm (copper foil standard sample, first batch of copper foil to be tested, and second batch) were tested separately.
[0065] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., transverse tensile strength and transverse elongation) are shown in Table 1.
[0066] Example 2
[0067] (1) Figure 1 As shown, a copper foil standard sample with a length and width of approximately 200*200 mm is placed on a smooth glass plate A. The copper foil is bent 180° (the fold is parallel to the longitudinal direction of the copper foil). The fold is covered with a smooth glass plate B (the outer fold of the copper foil is in contact with the glass plate B). A first pressure is applied to the fold through the glass plate B (the direction of the pressure is perpendicular to the copper foil surface, the pressure is 300 kg, and the pressure is applied for 5 seconds) to obtain a bent copper foil.
[0068] (2) Unfold the bent copper foil with the inner side facing upward and place it on glass plate A. Then, cover the crease with glass plate B (the inner crease of the copper foil is in contact with glass plate B). Apply a second pressure to the crease through glass plate B (the direction of the pressure is perpendicular to the surface of the copper foil, the pressure is 300 kg, and the pressure is applied for 5 seconds) to obtain a flat copper foil.
[0069] (3) Cut a rectangular copper foil with a length of 100 mm, a width of 15 mm, and a thickness of 6 μm from the above-mentioned flat copper foil as a test sample (in this test sample, the fold length is 15 mm, and the fold is perpendicular to the length direction of the test sample and is equidistant from the two ends of the test sample perpendicular to the length direction), and check to ensure that there is no obvious mechanical damage in the test sample except the fold line, and there are no burrs or flash on the edges;
[0070] (4) Adjust the original gauge length between the two clamps of the tensile testing machine to 50 mm, and fix the two ends of the test sample in the length direction on the two clamps respectively, wherein the length direction of the test sample is parallel to the axis of the clamps, and the test sample is kept flat; then start the testing machine and conduct the test. The test conditions include: the tensile speed is 50 mm / min. Obtain the tensile speed and elongation data of the test sample.
[0071] The same steps (1) to (4) and parameters as above were used to test the copper foil to be tested (first batch and second batch) with a length and width of about 200*200 mm.
[0072] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., longitudinal tensile strength and longitudinal elongation) are shown in Table 1.
[0073] The same steps (1) to (4) and parameters as above were used, with the only difference being that the fold in step (1) was parallel to the transverse direction of the copper foil, and copper foils with a length and width of approximately 200*200 mm (copper foil standard sample, first batch of copper foil to be tested, and second batch) were tested separately.
[0074] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., transverse tensile strength and transverse elongation) are shown in Table 1.
[0075] Example 3
[0076] (1) Figure 2As shown, an inner mold i and an outer mold ii (both having smooth inner surfaces) with the same fold angle (60°) are used, and a copper foil standard sample of about 200*200mm in length and width is placed between the inner mold i and the outer mold ii. Then, the inner mold i and the outer mold ii are overlapped and pressed, and a first pressure is applied to the crease through the inner mold i at the point where it contacts the inner surface of the bent copper foil (the direction of the pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil, and along the bisector of the mold fold angle and perpendicular to the axis of the fold, the pressure is 50kg, and the pressure is applied for 2s). Then, the inner mold i and the outer mold ii are removed to obtain a bent copper foil (the bending angle is 120°, and the fold is parallel to the longitudinal direction of the copper foil);
[0077] (2) The bent copper foil is unfolded with the inner side facing upwards and placed on glass plate A. The fold is then covered with glass plate B (the inner fold of the copper foil contacts the glass plate B). A second pressure is applied to the fold through glass plate B (the direction of the pressure is perpendicular to the surface of the copper foil, the pressure is 50 kg, and the pressure is applied for 2 seconds) to obtain a flat copper foil;
[0078] (3) Cut a rectangular copper foil with a length of 100 mm, a width of 15 mm, and a thickness of 6 μm from the above-mentioned flat copper foil as a test sample (in this test sample, the fold length is 15 mm, and the fold is perpendicular to the length direction of the test sample and is equidistant from the two ends of the test sample perpendicular to the length direction), and check to ensure that there is no obvious mechanical damage in the test sample except the fold line, and there are no burrs or flash on the edges;
[0079] (4) Adjust the original gauge length between the two clamps of the tensile testing machine to 50 mm, and fix the two ends of the test sample in the length direction on the two clamps respectively, wherein the length direction of the test sample is parallel to the axis of the clamps, and the test sample is kept flat; then start the testing machine and conduct the test. The test conditions include: the tensile speed is 50 mm / min. Obtain the tensile speed and elongation data of the test sample.
[0080] The same steps (1) to (4) and parameters as above were used to test the copper foil to be tested (first batch and second batch) with a length and width of about 200*200 mm.
[0081] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., longitudinal tensile strength and longitudinal elongation) are shown in Table 1.
[0082] The same steps (1) to (4) and parameters as above were used, with the only difference being that the fold in step (1) was parallel to the transverse direction of the copper foil, and copper foils with a length and width of approximately 200*200 mm (copper foil standard sample, first batch of copper foil to be tested, and second batch) were tested separately.
[0083] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., transverse tensile strength and transverse elongation) are shown in Table 1.
[0084] Example 4
[0085] The method of Example 1 was followed, with a copper foil standard sample and two batches of copper foil to be tested as test objects, except that steps (1) and (2) were repeated three times (wherein the conditions for applying the first and second pressures remained unchanged in different operations, and the copper foil was bent in the same direction each time), followed by steps (3) and (4). Other conditions were the same as in Example 1.
[0086] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., longitudinal tensile strength and longitudinal elongation) are shown in Table 1.
[0087] The test results of the copper foil standard sample and the two batches of copper foil to be tested (i.e., transverse tensile strength and transverse elongation) are shown in Table 1.
[0088] Comparative Example 1
[0089] (1) Cut a rectangular copper foil with a length of 100 mm, a width of 15 mm, and a thickness of 6 μm from the copper foil (the first batch) with a length and width of about 200*200 mm (the length direction of the rectangular copper foil is parallel to the longitudinal direction of the copper foil) as a test sample, and check to ensure that there is no obvious mechanical damage in the test sample except for the fold line, and there are no burrs or flash on the edges;
[0090] (2) Adjust the original gauge length between the two clamps of the tensile testing machine to 50 mm, and fix the two ends of the test sample in the length direction on the two clamps respectively, wherein the length direction of the test sample is parallel to the axis of the clamps, and the test sample is kept flat; then start the testing machine and test, and the test conditions include: the tensile speed is 50 mm / min. Obtain the tensile speed and elongation data of the test sample.
[0091] The same steps (1) to (2) and parameters as above were used to test copper foil (the second batch) with a length and width of approximately 200*200 mm.
[0092] The test results of the two batches of copper foil (i.e., longitudinal tensile strength and longitudinal elongation) are shown in Table 1.
[0093] The same steps (1) to (2) and parameters as above were used, with the only difference being that in step (1), a rectangular copper foil with a length of 100 mm, a width of 15 mm, and a thickness of 6 μm (the length direction of the rectangular copper foil was parallel to the transverse direction of the copper foil) was cut as a test sample, and copper foils with a length and width of approximately 200*200 mm (the first batch and the second batch) were tested separately.
[0094] The test results of the two batches of copper foil (i.e., transverse tensile strength and transverse elongation) are shown in Table 1.
[0095] Table 1
[0096]
[0097] From the results in Table 1, it can be seen that Examples 1-4 adopt the test method of the present invention. Under different test parameters, the tensile strength and elongation of the copper foil (second batch) are greater than the copper foil standard sample, while the tensile strength and elongation of the copper foil (first batch) are lower than the copper foil standard sample. The tensile strength and elongation performance of the copper foil (second batch) exceed the copper foil (first batch) to varying degrees, which is consistent with the state of the pole pieces seen after the battery cells using these two batches of copper foil are disassembled (after the battery cells are disassembled, the negative pole pieces using the copper foil (second batch) have no cracks, while the negative pole pieces using the copper foil (first batch) have cracks), indicating that the test method of the present invention can effectively characterize the fatigue resistance of the copper foil. Among them, in Example 1, the test data results of the two batches of copper foil have significant differences, especially in terms of elongation, there is a gap of nearly one-fold. The test results are consistent with the battery cell disassembly results, which can well characterize and identify the fatigue resistance differences of different batches of copper foil.
[0098] Compared with Examples 1-4, the data results of the copper foil standard sample, copper foil (first batch) and copper foil (second batch) measured by the method of Comparative Example 1 are consistent, but the electrode states seen after disassembly of the battery cell are different, which cannot effectively characterize and identify the fatigue resistance and differences of copper foils of different batches.
[0099] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A method for testing the fatigue resistance of copper foil, characterized in that: The method includes: (1) bending a copper foil and applying a first pressure to obtain a bent copper foil, wherein the bent copper foil has a crease formed by the bending; and the first pressure is applied to the crease; (2) unfolding the bent copper foil and applying a second pressure to the crease to obtain a flat copper foil; (3) cutting at least a portion of the flat copper foil as a test sample, wherein the test sample contains at least a portion of the fold; (4) performing a tensile test on the test sample, and evaluating the fatigue resistance of the copper foil according to the measured tensile strength and elongation; Among them, evaluating the fatigue resistance of the copper foil includes: using the method to test and obtain the tensile strength and elongation data of the copper foil standard sample, as well as the tensile strength and elongation data of the copper foil to be evaluated; comparing the tensile strength and elongation data of the copper foil to be evaluated with the tensile strength and elongation data of the copper foil standard sample: when the tensile strength and elongation of the copper foil to be evaluated are not lower than those of the copper foil standard sample, it is considered that the fatigue resistance of the copper foil to be evaluated meets the requirements; when at least one of the tensile strength and elongation of the copper foil to be evaluated is lower than that of the copper foil standard sample, it is considered that the fatigue resistance of the copper foil to be evaluated cannot meet the requirements or has the risk of cracking during use.
2. The method according to claim 1, wherein: The copper foil has a thickness of 3-30 μm and a surface density of 25-270 g / cm 2 .
3. The method according to claim 1 or 2, wherein: In step (1), the bending causes the copper foil to form a bending angle of 1-180°.
4. The method according to claim 3, wherein: In step (1), the bending causes the copper foil to form a bending angle of 90-180°.
5. The method according to claim 3, wherein: In step (1), when the bending angle is 180°, the conditions for applying the first pressure include: the pressure direction is perpendicular to the surface of the copper foil; the pressure magnitude is 0.01-500kg; and the time is 1-86400s.
6. The method according to claim 5, wherein: In step (1), when the bending angle is 180°, the conditions for applying the first pressure include: the pressure direction is perpendicular to the surface of the copper foil; the pressure magnitude is 20-100 kg; and the time is 2-60 s.
7. The method according to claim 3, wherein: In step (1), when the bending angle is less than 180°, the conditions for applying the first pressure include: the direction of pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil; the pressure magnitude is 0.01-500kg; and the time is 1-86400s.
8. The method according to claim 7, wherein: When the bending angle is less than 180°, the conditions for applying the first pressure include: the pressure direction is from the inner side of the bent copper foil to the outer side of the bent copper foil; the pressure magnitude is 20-100 kg; and the time is 2-60 s.
9. The method according to claim 1 or 2, wherein: In step (2), the conditions for applying the second pressure include: the direction of the pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil; the pressure magnitude is 0.01-500kg; and the time is 1-86400s.
10. The method according to claim 9, wherein: In step (2), the conditions for applying the second pressure include: the direction of the pressure is from the inner side of the bent copper foil to the outer side of the bent copper foil; the pressure is 20-100 kg; and the time is 2-60 s.
11. The method according to claim 1 or 2, wherein: Step (1) and step (2) can be repeated 0-20 times.
12. The method according to claim 11, wherein: Step (1) and step (2) can be repeated 0-1 times.
13. The method according to claim 11, wherein: When step (1) and step (2) are repeated, the position of the crease formed by each bending is the same.
14. The method according to claim 12, wherein: When steps (1) and (2) are repeated, the position of the crease formed by each bending is the same.
15. The method according to claim 1 or 2, wherein: In step (3), the thickness of the test sample is the same as the thickness of the copper foil and the shape is rectangular.
16. The method according to claim 15, wherein: The test sample has a length of 20-200 mm and a width of 5-50 mm.
17. The method according to claim 15, wherein: In step (3), in the test sample, at least part of the folds are perpendicular to the length direction of the test sample and are equidistant from both ends of the test sample that are perpendicular to the length direction.
18. The method according to claim 16, wherein: In step (3), in the test sample, at least part of the folds are perpendicular to the length direction of the test sample and are equidistant from both ends of the test sample that are perpendicular to the length direction.
19. The method according to claim 1 or 2, wherein: In step (4), the conditions of the tensile test include: a tensile speed of 10-500 mm / min.
20. The method according to claim 19, wherein: In step (4), the conditions of the tensile test include: a tensile speed of 50-100 mm / min.
Citation Information
Patent Citations
Method for testing ultimate compaction density of lithium ion battery pole pieces
CN107727567A